Pengaruh Citra Merek dan Harga Terhadap Kepuasan serta Implikasinya Pada Loyalitas Pelanggan pada Prima.Network di Jember - Gerry Hendra Setiawan; Nasrullah Nasrullah; Lukman Hadi (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The aims of this study were: 1) To determine the significant effect of brand image on Prima.Network customer satisfaction in Jember. 2) To determine the significant effect of Price on Prima.Network Customer Satisfaction in Jember. 3) To determine the significant effect of Brand Image on Prima.Network Customer Loyalty in Jember. 4) To determine the significant effect of Price on Prima.Network Customer Loyalty in Jember. 5) To determine the significant effect of Satisfaction on Prima.Network Customer Loyalty in Jember. 6) To determine the significant effect of Brand Image on Satisfaction and Its Impact on Prima.Network Customer Loyalty in Jember. 7) To determine the significant effect of Price on Satisfaction and its Impact on Prima.Network Customer Loyalty in Jember. The type of research conducted in this research is descriptive research using survey methods. The population in this study is the community or users of Prima.Network services in Jember, totaling 400 people. The sampling technique used was the Slovin formula, so a sample of 200 Prima.Network customers was taken in Jember. The analytical method in this study was carried out using the Structural Equation Model (SEM). The model used is multiple regression analysis. The results of this study indicate that: 1) There is an influence of Brand Image on Customer Satisfaction. 2) There is an effect of Price on Customer Satisfaction. 3) There is an influence of Brand Image on Customer Loyalty. 4) There is an effect of Price on Customer Loyalty. 5) There is an influence of Customer Satisfaction on Customer Loyalty. 6) There is an influence of Brand Image on Customer Satisfaction. 7) There is an effect of Price on Satisfaction and its Impact on Customer Loyalty